Tinjauan Historiografi Tentang Kekerasan di Timor Timur (1976-1999) dalam Sastra Indonesia: Saksi Mata - Fadhil Hudaya; Mestika Zed; Etmi Hardi (PAMA Aksara, 2019)
This article aims to explain how the violent condition in Timor Timur from integration to disintegration with Indonesia (1976-1999). The background of the research is to flashback the “Orde Baru” era about the depiction of violence in literature work. This article is a historiography study in a short story called Saksi Mata by Seno Gumira Ajidarma. The writing process used literary and mimetic methods to analyze the data, which is observing the literary content with a realistic approach that was found in scientific study. The result of this research was representation and reality that was shown about pathetic explanation and touched humanity on how to further step towards to reveal the truth that was still hidden.